Pediatric Distal Femur Fixation by Proximal Humeral Plate - Abdelgawad, Amr Atef; Kanlic, Enes M. (The Journal of Knee Surgery, 2013)
Distal femoral metaphyseal fractures are common injuries in children. Multiple treatment options have been described for this type of injury. For older children with distal metaphyseal fracture, there is still no optimal method of fixation. We propose that the commonly used proximal humeral plate can provide good method of fixation for this fracture in adolescents. Two children (12 and 14 years old) with distal metaphyseal femoral fracture were treated with proximal humeral plate. We describe the surgical technique and postoperative management. The two children healed with good alignment and full range of motion of the knee. No external immobilization (other than knee immobilizer for the first 2 weeks) was used. We concluded that proximal humeral plate can provide adequate fixation for teenagers with distal femoral metaphyseal fracture. It is readily available; provide multiple options for screw fixation in the distal part of the fracture and fits easily on the distal part of the femur proximal to the physis.
Keywords: fracture; distal femur; pediatric; children; adolescent; metaphyseal fracture; proximal humeral plate; knee; internal fixation